STRATEGI PENINGKATAN DAYA SAING INDUSTRI BATIK DI KOTA PEKALONGAN - , Erna Setianingrum, Dr. Eko Suwardi, M.Sc., CMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the strategy of improving the competitiveness of batik industry in Pekalongan through questionnaires and perferensi respondents (community and government) of the condition and situation of the development of batik industry today. Primary data were collected using purposive sampling with a sample of 114 respondents, 13 from government, and 103 from the community consisting of 64 batik artisans, 27 students, 5 of 5 from the media and batik. Tool association analysis is a SWOT analysis for the determine the position and alternative strategies used to improve the competitiveness of the batik industry in Pekalongan criteria with regard dimensions strengths,weaknesses, opportunities and threats. The results of the SWOT analysis in the study show that the conditions encountered in Pekalongan batik improve the competitiveness of the industry are in a favorable situation in which priority to use force to prevent a threat to the use of alternative strategies is the strategy ST (quadrant I). The strategy supports an aggressive growth policy to maximize the power of aspects that have a high score and minimize the threat aspects that have the highest scores.